Immunoexpression of the relaxin receptor LGR7 in breast and uterine tissues of humans and primates - Milde-Langosch Karin; Bartsch Olaf; Telgmann Ralph; Pohnke Yvonne; Balvers Marga; Ivell Richard; Bamberger Ana-maria; Einspanier Almuth (BMC, 2003)
Abstract Background The receptor for the peptide hormone relaxin has recently been identified as the heptahelical G-protein coupled receptor, LGR7. In order to generate molecular tools with which to characterize both in vivo and in vitro expression of this receptor in human and primate tissues, specific monotypic antibodies have been generated and applied to a preliminary analysis of human and primate female reproductive tissues. Methods Three peptide sequences were identified from the proposed open reading frame of the cloned LGR7 receptor gene, representing both extracellular and intracellular domains. Two to three rabbits were immunized for each epitope, and the resulting sera subjected to a systematic validation using cultured cells transiently transfected with a receptor-expressing gene construct, or appropriate control constructs. Results Human and monkey (marmoset, macaque) endometrium showed consistent and specific immunostaining in the stromal cells close to glands. Staining appeared to be more intense in the luteal phase of the cycle. Weak immunostaining was also evident in the endometrial epithelial cells of the marmoset. A myoma in one patient exhibited strong immunostaining in the circumscribing connective tissue. Uterine expression was supported by RT-PCR results from cultured primary endometrial and myometrial cells. Human breast tissue (healthy and tumors) consistently indicated specific immunostaining in the interstitial connective (stromal) tissue within the glands, but not in epithelial or myoepithelial cells, except in some tumors, where a few epithelial and tumor cells also showed weak epitope expression. Conclusions Using validated monotypic antibodies recognizing different epitopes of the LGR7 receptor, and from different immunized animals, and in different primate species, a consistent pattern of LGR7 expression was observed in the stromal (connective tissue) cells of the endometrium and breast, consistent also with the known physiology of the relaxin hormone.